Analisis Perilaku Pekerja Gondola PT. Waringin Megah Proyek Springhill Condotel Lampung - Zamahsjari Sahli; Triyanto Triyanto (Politeknik Kesehatan Tanjung Karang, 2018)
This research was conducted at Springhill Condotel Lampung to find out and dig deeper into the behavior of gondola workers. This study used a qualitative study approach. Information collection and retrieval is obtained through observation, in-depth interviews, and document studies. The supporting factors that have not supported the gondolier workers to behave safely are knowledge of the hazards, the bad perception about Personal Protective Equipment (PPE), and the undisciplined attitude of the workers Using PPE. On the enabling factor, it was found out that the availability of PPE and the existing rules in the project enables gondola workers to behave safely, but still found unsafe acts. And on the reinforcement factor, less supervision was found from supervisors and safety. Company to provide information about hazards of gondolas, tighten the control of PPE, and provide safe behavior training. Gondola workers to ask supervisors and OSH sections on things they do not know, change poor perceptions better about the use of PPE, and to improve negative attitudes in the use of PPE and regulations.